ANIMAL ISSUES IN THE POLITICAL AND LEGAL SPHERE IN RUSSIA AND ABROAD - BEZNOSOVA Yana Viktorovna; MINEEVA Tatiana Germanovna; ROMANOVSKAYA Vera Borisovna (Правовое государство: теория и практика)
In Russia, the issue of the status of animals is at a medieval level, and it is extremely difficult to resolve it without ethical reflection. The purpose of the article is to consider a current problem concerning the status of animals. The authors analyse two opposing points of view on the status of animals in modern Russian society, conditioned by historical, cultural, religious and ethical factors. Particular attention is paid to the use of animals in agriculture, livestock farming, food production, as well as in circuses, zoos and oceanariums. The research methods include a comparative analysis of the positions of animal rights advocates and their opponents, as well as a study of legislative initiatives in this area, both in Russia and abroad. Results: the authors propose to develop a concept for the protection of animal rights and welfare, to toughen penalties for cruel treatment of farm animals, as well as to adopt standards for their maintenance and strictly control their observance.